Production and economic viability of feedlot beef cattle categories - Santos, Petrônio Batista dos; Santana Junior, Hermógenes Almeida de; Araújo, Marcos Jacome de; Oliveira, Aracele Prates de; Freitas, Tiago Brandão; Viana, Pablo Teixeira (Acta Scientiarum. Animal Sciences, 2017)
This study was realized to evaluate the production and economic viability of finished beef cattle in feedlot in the Cerrado biome of Piauí State, Brazil. One hundred and fifty cattle -50 bulls (B) with an body weight of 283.0 ± 20.82 kg, at 30 months of age; and 100 cull cows (CC) with an body weight of 296.1 ± 17.80 kg, at 100 months of age- were used in a completely randomized design. The animal performance indicators for the evaluation of economic viability were initial age (months), slaughter age (months), was initial body weight (kg), final body weight (kg), daily feed intake (kg animal-1; kg kg-1 BW), diet cost (R kg-1 of diet), cost of kg produced (R kg-1 produced), and average price of the kg of meat for finishing (R). The CC consumed more sorghum silage and concentrate than B (p < 0.05).There was a difference between the categories (p < 0.05) for gross revenue, balance, opportunity cost, and net revenue per animal, with higher values found for the steer category. The animal category did not affect the profitability of the system, although the bulls provided lower revenues than cull cows.